Prediksi konsumsi beras menggunakan metode regresi linear pada sistem kotak beras cerdas - Mulia Hanif; Maman Abdurohman; Aji Gautama Putrada (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2020)
Currently, the smart rice box has applied the Internet of Things (IoT) but without prediction of rice runs out which shows the amount of rice consumption. This study applies linear regression to predict the rice runs out in an IoT-based smart rice box and analyzes its performance. The prediction used the dataset obtained by measuring a smart rice box equipped with a load cell weight sensor and Hx711 module. The weight sensor accuracy was an RMSE of between 56 and 170 grams. The linear regression method applied to the smart rice box to predict rice running out has an MSE value of 0.2588 with a prediction window of 43 days. An R-squared value of less than one is obtained with a predictive threshold of 24 days.